Community-Driven Programming: Offering Coding and Robotics Classes in your Library. - Carrier, Mary (Information Technology & Libraries, 2023)
Mary Carrier serves as the Technology & Growth Specialist for the four counties of the Mohawk Valley Library System in Schenectady, New York. Prior to this position, Mary dedicated over 15 years to teaching digital literacy and technology trends at the Clifton Park-Halfmoon Public Library, a suburban public library that has over 40,000 registered patrons and 1,500 visitors per day. The community has a strong presence in youth and family programs and is a popular place for teens and children to learn, play, and create. In 2015, she began offering coding and STEM classes to children and teens at the library and in the community as outreach programs. Mary will share her expertise in technology programming for children and teens and the importance of planning, preparing, and testing curriculum for coding and robotics classes.